2004
DOI: 10.1088/0953-8984/16/6/003
|View full text |Cite
|
Sign up to set email alerts
|

Glass transition temperatures of polymer thin films monitored by Raman scattering

Abstract: We report measurements of the glass transition temperature (T g ) in thin freestanding polymer films of polystyrene (PS) by means of confocal Raman spectroscopy. The paper introduces Raman spectroscopy as a novel method for the determination of T g in polymer thin films. We find excellent agreement between Raman scattering and previously reported values of T g obtained from either Brillouin scattering or ellipsometry. Further possible applications of the method to more complex conjugated polymers are briefly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 36 publications
11
63
0
Order By: Relevance
“…Liem et al 35 used Raman spectroscopy to determine T g reductions for free-standing PS films (MW ¼ 600 kg mol À1 ); in a 50-nm-thick PS film, they observed that T g was decreased by slightly more than 30 K relative to bulk PS, in approximate agreement with data by Dutcher and coworkers. 28,29 Miyazaki et al 36 used x-ray reflectivity to determine T g values for two MWs (303 kg mol À1 and 2890 kg mol…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Liem et al 35 used Raman spectroscopy to determine T g reductions for free-standing PS films (MW ¼ 600 kg mol À1 ); in a 50-nm-thick PS film, they observed that T g was decreased by slightly more than 30 K relative to bulk PS, in approximate agreement with data by Dutcher and coworkers. 28,29 Miyazaki et al 36 used x-ray reflectivity to determine T g values for two MWs (303 kg mol À1 and 2890 kg mol…”
supporting
confidence: 61%
“…10 Beyond the studies by Dutcher and coworkers, three other studies have been reported that provide direct T g determinations of single-layer free-standing polymer films. [34][35][36] Mattsson et al 34 used Brillouin scattering to demonstrate that the T g -confinement effect in free-standing PS films is independent of MW for MWs less than $ 350 kg mol…”
Section: Experimental Support For This Hypothesis Was Provided In 200mentioning
confidence: 99%
“…The depression of the glass transition temperature with the decrease of film thickness was shown in numerous studies. 13,17,21 Thus, our results are in agreement with earlier published ones. Fig.…”
Section: Resultssupporting
confidence: 93%
“…The determination of the glass transition temperature has been the subject of through studies over last 50 years. Nowadays, there are many methods for determining the glass transition temperature of bulk amorphous and liquid crystalline polymers such as differential scanning calorimetry 15 , dynamic mechanical analysis 16 , Raman scattering 17 , Brillouin scattering 18 and others. However, most of these methods have a low sensitivity to the sub-100 nm thick polymer films.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric spectroscopy has become the standard technique for experimentally investigating the relaxational dynamics associated with the glass-transition, 5,6 and such measurements have uncovered a number of characteristic relaxation fingerprints that occur within particular frequency windows, with the two most common being the primary a-relaxation (E10 À6 -10 3 Hz), corresponding to entire-molecule rearrangement, and the secondary JohariGoldstein ( JG) b (E10 À6 -10 9 Hz) relaxation, which has been suggested as a representing a special class of secondary relaxations strongly linked to the a number of physical properties. [7][8][9] But while dielectric spectroscopy probes the (relatively low) frequency relaxation of electric-dipole vectors, numerous other a Department of Chemical Engineering and Biotechnology, University of Cambridge, techniques have been used to characterise the properties and glass-transition temperatures of glasses, including neutron scattering, 10 Brillouin light scattering (BLS), 11 dynamical mechanical analysis (DMA), 12 Raman scattering 13 and, more recently, terahertz time-domain spectroscopy (THz-TDS), 14 amongst many others. 15,16 In general, each of these methods were found to be sufficiently sensitive for detecting the a-and b-relaxation fingerprints, as well as the corresponding glass transitions (e.g.…”
Section: Introductionmentioning
confidence: 99%